Treatment with 5-Azacytidine improves clinical outcome in high-risk MDS patients in the 'real life' setting: A single center observational study. Issue 1 (2nd January 2016) - Papageorgiou, Sotirios G.; Vasilatou, Diamantina; Kontos, Christos K.; Foukas, Periklis; Kefala, Maria; Ioannidou, Eleni-Dikaia; Bouchla, Anthi; Bazani, Efthymia; Dimitriadis, George; Pappa, Vasiliki
Abstract : Objectives : The demethylating factor 5-Azacytidine (5-AZA) improves survival of patients with myelodysplastic syndromes (MDS) in randomized control trials but the results in 'real life' are controversial. Methods : In this retrospective study, we evaluated the outcome of 56 high-risk MDS patients who were treated with 5-AZA between 2005 and 2013. 5-AZA was administered in an outpatient basis at a dose 75 mg/m 2 s.c. with the following schedule: 5 days on/weekend off/2 days on (5/2/2). Results : The overall response rate (ORR) was 50%; 21.2% patients achieved complete response (CR), 3.8% partial response (PR), and 25% hematologic improvement (HI); 34.6% had stable disease (SD) and 15.4% showed progressive disease (PD). The estimated median event free survival (EFS) and overall survival (OS) were 11 and 17 months, respectively. Interestingly, the estimated time to acute myeloid leukemia transformation was 30 months, which refers to patients who responded to AZA treatment or remained stable. Patients who responded to the 5-AZA achieving CR, PR, and HI had better EFS and OS compared to the patients who had SD or PD. In addition, Δ WHO Classification-based Prognostic Score System (ΔWPSS), which represents the improvement of WPSS risk group before and after treatment, was associated with significantly improved OS and better EFS. Finally, the response to treatment was not associated with the expression of p53. Conclusions : In conclusion, 5-AZA is an effective treatment for high-risk MDS. Improved OS and EFS were found mainly in patients who responded to the treatment while ΔWPSS seems to represent a promising future prognostic tool.